PHYSICAL THERAPY OF ATHLETES WITH KNEE TENDENITIS (Physical Culture and Sport: Scientific Perspective, 2024)
The article deals with the issue of physical therapy for athletes with patellar tendonitis. It has been established that patellar tendonitis is a common problem among athletes, especially in those sports that involve jumping and sudden changes in direction. It has been determined that physical therapy is one of the main methods of treating this pathology, which is confirmed by relevant scientific research. A comprehensive analysis of Ukrainian and foreign studies on the effectiveness of various methods of physical therapy for patellar tendonitis among athletes with different levels of physical fitness, such as muscle strengthening exercises, stretching, massage and other methods, was conducted. The methods of treatment of patellar tendinopathy identified by foreign scientists, including rest, activity modification, anti-inflammatory drugs, injection therapy, taping, eccentric exercises, extracorporeal shock wave therapy, are considered, percutaneous electrolysis and surgery, as well as methods proposed by Ukrainian researchers - kinesiotaping, exercise therapy, shock wave therapy, plasmolifting, drug therapy and corticosteroid injections. Additional methods that can be effective in the physical therapy of patellar tendonitis are highlighted: massage, which improves blood circulation, reduces swelling and muscle spasm, manual therapy, which helps restore joint and soft tissue mobility, laser therapy, which reduces inflammation and accelerates regeneration processes. The article also considers preventive methods, the use of which will help prevent the occurrence of patellar tendinitis in athletes, covered in publications of foreign and domestic scientists. According to Ukrainian research, prevention of patellar tendonitis includes: warming up before training to prepare the muscles for the load, gradual increase in load (avoiding sudden jumps in training load), strengthening the thigh muscles through regular strength training, and proper exercise technique to avoid overloading the tendon. According to foreign studies, static stretching, core stability exercises, foot orthosis, shock-absorbing insoles, and hormone replacement therapy in women are considered as the most common preventive methods for patellar tendonitis. It is emphasized that early intervention and initiation of physical therapy increase the chances of full recovery of an athlete with patellar tendonitis.
Keywords: patellar tendonitis; physical therapy of athletes; rehabilitation; jumper's knee; muscle strengthening